Implementation Learning Strategy Think Talk Write to Improve Student Learn Motivation on Biology Class VIII D SMP Negeri 22 Surakarta Class Year 2010/201 - Listiawan, Dwi; Maridi, Maridi; Probosari, Riezky Maya (Universitas Sebelas Maret, 2012)
The purpose of this study was to increasing students motivation to study biology with implementation of Think talk write learning strategy through increased motivation to learn.This research was a classroom action research through the implementation of Think talk write learning strategy. The research was conducted in two cycles, with each cycle consisting of four phases, namely planning, implementation actions (acting), observation, and reflection. The subject were students in grade VIII D SMP Negeri 22 Surakarta academic year 2010/2011. The sources of data derived from teacher and student information, places and events of the ongoing learning activities, and documentation. The techniques and data collection tool used observation, questionnaires, and interviews. The data was analysized techniques with descriptive analysis techniques. The data validation used triangulation techniques.The result proved that the implementation of the classroom action research through the application of Think talk write learning strategy write could be improving the motivation of learning biology in grade VIII D SMP Negeri 22 Surakarta.. Based on observations, questionnaires and interviews. The percentage of each indicator is based on students motivation observation sheets, precycle 39,05%, first cycle 69,52% and second cycle 89,52%. Based on these results, it could be concluced that the implementation of Think talk write learning strategy was increasing the students motivation to learning Biology in grade VIII D SMP Negeri 22 Surakarta academic year 2010/2011. Key Words: learning strategy Think Talk Write, learn motivation on biology